The Impact of the Rice Milling Industry on Tulang Bawang: A Sociological Approach - Komang Ariyanto (Strata Social and Humanities Studies, 2023)
The industrial sector is considered as one of the biggest polluters and waste generators. Since the big industry started, pollution has increased rapidly. The result of the production process is not only in the form of finished goods that can be sold, but the remaining production waste can damage the environment. The purpose of this study is to describe the sociological impacts of the existence of the rice milling industry. This researcher used a literature study by reading, processing, and writing readings from various reference sources. The results of the study show that this industry has a positive impact on improving the welfare of the community and for the benefits of industrial owners. In addition, it has a negative impact on the environment, for workers, and for the surrounding community. So that prevention and control are needed from the workers themselves, the government through policy formation, control from the surrounding community and the creation of an industrial climate by taking into account Environmental Impact Analysis, environmentally friendly industries and the principles of eco-efficiency and zero waste.